Blockade of 5-Hydroxytryptamine 2A Receptor Attenuates Precipitation of Naloxone-Induced Withdrawal Symptoms in Opioid-Exposed Mice - Li, Bing; Jiang, Junyu; Zhou, Li; Tao, Xinrong; Sun, Qixian; Liu, Jiaxin; Liu, Yang; Pang, Gang (Frontiers in Behavioral Neuroscience, 2022)
Heroin addiction and persistent dependency have evolved into an emerging global epidemic inducing significant clinical and socio-economic burdens along with devastating medical consequences. Accumulating evidence reveals that chronic drug exposure alters the expression and functional activity of 5-hydroxytryptamine (serotonin) 2A receptors (5-HT2ARs) in the brain. Furthermore, pharmacological blockade of 5-HT2ARs exhibits an attenuation of cue-induced cocaine craving behaviors. In this study, we explored the mechanistic influence of 5-HT2ARs on heroin withdrawal-induced behavioral changes in mice. Black C57BL/6J mice were administered with gradually increasing (10 to 50 mg/kg bodyweight over 4.5 days) doses of heroin to induce heroin dependency before naloxone was used to precipitate withdrawal symptoms. MDL100907, a selective and potent 5-HT2AR antagonist, attenuated naloxone-precipitated withdrawal symptoms in these mice. In addition, the level of 5-HT2AR in the dorsomedial prefrontal cortex (dmPFC) was also increased significantly, while the phosphorylation level of the extracellular signal-regulated kinase (p-ERK) in the dmPFC was decreased after heroin treatment. In conclusion, these results suggest that 5-HT2ARs might be involved in the development of opioid dependency, and the pharmacological blocking of 5-HT2ARs might be a new therapeutic strategy for treating heroin abuse.